Influence of Ternary Emulsifier Mixtures on Oxidative Stability of Nanoemulsions Based on Avocado Oil - Arancibia-Aguilar, C; Riquelme-Hinojosa, N (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
The aim of this work was to study the effect of two emulsifiers (M1: SL-soy lecithin, Tw80-Tween 80 and CasCa-calcium caseinate andM2: SL-soy lecithin, Tw80-Tween 80 and SE-sucrose esters) on the oxidative stability of avocado oil-based nanoemulsions. Oil-in-water nanoemulsions were prepared using 3.6% w/w of two emulsifier mixtures, which were optimized by mixture experimental design in order to minimize particle size (PS) and polydispersity index (PdI). Then, the oxidative stability of nanoemulsions was evaluated through both an induction period and a quantification of hydroperoxides and thiobarbituric acid reactive species (TBARs) under accelerated storage conditions. The simplex-centroid mixture design showed that PS and PdI varied when proportions of different emulsifiers were modified, obtaining an optimized concentration for each mixture of: 85% SL, 10% Tw80 and 5%CasCa (M1) and 85% SL, 7.4% Tw80 and 7.6% SE (M2) that produced nanoemulsions with PS ~116 nm and PdI < 0.2. Nanoemulsions elaborated with M1 and M2 presented similar particle characteristics and physical stability to the control sample with Tw80. However, M1 nanoemulsions were more stable against lipid oxidation, since they showed the highest induction period and lower formation of hydroperoxides and TBARs during storage. © 2020 by the authors.